Analysis of Factors Related to Near Miss among Nurses - Kania Nayuri Nugroho; Abdul Rohim Tualeka; Innaha Ilma Wardaya (Universitas Airlangga, 2023)
Introduction: Nurses are an important human resource in hospital health services with a high-risk workplace that can cause accidents or occupational diseases. This study aims to analyze the relationship between near-miss knowledge, occupational health and safety skill, and work equipment with the occurrence of near-miss among nurses. Method: This research used a cross-sectional design. The population of this study was nurses in Ploso Regional Public Hospital. The samples were chosen using the purposive sampling method with a number of 53 nurses out of 56 population of nurses with consideration of safety during the Covid-19 pandemic. The independent variables were near-miss knowledge, occupational health and safety skill, and work equipment. The dependent variable was the occurrence of the near-miss. The data was collected using questionnaires. The data analysis technique used was the Pearson correlation test. Result: The result of the questionnaire showed most of the samples had high near-miss knowledge, high occupational health and safety skill, and good work equipment. The occurrence of near-miss among the nurses was mostly medium. The Pearson correlation test result showed that the correlation of near-miss knowledge was weak, occupational health and safety skill were fairly strong, and work equipment was weak. Conclusion: The relationship between near-miss knowledge with the occurrence of near-miss has a weak correlation with positive direction, the relationship between occupational health and safety skills and the occurrence of near-miss has a fairly strong correlation with negative direction, and the relationship between work equipment and the occurrence of near-miss has a weak correlation with negative direction.